2021
DOI: 10.3389/fcvm.2021.614204
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Predictive Model for Coronary Artery Disease Using Machine Learning

Abstract: Early identification of coronary artery disease (CAD) can prevent the progress of CAD and effectually lower the mortality rate, so we intended to construct and validate a machine learning model to predict the risk of CAD based on conventional risk factors and lab test data. There were 3,112 CAD patients and 3,182 controls enrolled from three centers in China. We compared the baseline and clinical characteristics between two groups. Then, Random Forest algorithm was used to construct a model to predict CAD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Therefore, maybe the low prevalence of females who smoke in this region is the reason for not seeing smoking status as a contributing variable for CVD prediction. HDL is famous as “good cholesterol”, so low levels of HDL are known as a CVD risk factor [ 15 , 57 ]. However, some studies failed to prove the prevention effect of controlling the levels of HDL on CVD events [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maybe the low prevalence of females who smoke in this region is the reason for not seeing smoking status as a contributing variable for CVD prediction. HDL is famous as “good cholesterol”, so low levels of HDL are known as a CVD risk factor [ 15 , 57 ]. However, some studies failed to prove the prevention effect of controlling the levels of HDL on CVD events [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high efficiency and accuracy, random forest algorithms as a type of ensemble learning method have been successful in the prediction and identification of clinical disease ( Savargiv et al, 2021 ). Wang et al developed a model to predict coronary artery disease using a random forest algorithm, which had good discrimination abilities ( Wang et al, 2021 ). Another study demonstrated that endobronchial optical coherence tomography based on a random forest algorithm was effective for the detection of early malignant pulmonary disease ( Ding et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…RF is a supervised ensemble learning method and based on decision trees that were built from the variable set. RF performs well in solving the overfitting problem of unbalanced data [ 16 ]. XGBoost is another ensemble tree algorithm.…”
Section: Methodsmentioning
confidence: 99%